The role of the judge in the preparation of a civil case to trial (Journal of actual problems of jurisprudence, 2018)
The article focuses on the role of civil judge preparing cases for trial. Preparation of cases for trial is seen as a mandatory stage of civil process. Author dwelled on the actions of the judge preparing the case for trial, notes the importance of the judge’s ruling on the preparation of cases for trial. In the article the author also address changes in terms of preparation for trial on the new Code of Civil Procedure of RK.Key words: Preparation of civil cases, legal definition, the term preparation of the case.